Xsan quick-reference guide : a handbook for Xsan setup and administration - Green, Adam B. (Apple Pro training series., 2005)
Apple’s exciting new enterprise-class file system offers high-speed access to centralized shared data. This handy booklet provides invaluable setup, configuration, and troubleshooting tips. Designed as a reference, you'll find clear explanations of everything from multiple-seat topologies to working with Xsan Admin software, plus useful illustrations and schematic diagrams. A must for every Xsan installation.